DEVELOPMENT OF THE ALGORITHM FOR IDENTIFICATION OF THE LEVEL OF VIBRIO CHOLERAE CTXA AND TOXR GENE EXPRESSION USING RT-PCR WITH REAL-TIME HYBRIDIZATION-FLUORESCENT REGISTRATION OF RESULTS - A. A. Kritsky; N. B. Cheldyshova; I. V. Tuchkov; N. I. Smirnova (Проблемы особо опасных инфекций, 2017)
Objective of the study is to design the algorithm for assessment of expression of the structural and regulatory virulence Vibrio cholerae genes by the model of ctxA and toxR genes encoding and controlling biosynthesis of cholera toxin.Materials and methods. Utilized were 10 strains of Vibrio cholerae, classical and El Tor biovars. Cloning of gene fragments was carried out through transformation and ligation. RT-PCR was done in “BIS M112” and “Rotor-GeneQ” amplifiers. Processing of the results was performed by means of the software package in set with Rotor-GeneQ (Software 1.8.17.5).Results and conclusions. Developed has been the algorithm for evaluation of the level of expression of V. cholerae ctxA and toxR genes applying RT-PCR with real-time hybridization-fluorescent registration of results. The stated algorithm allows for rapid and effective statistically significant specification of the expression of structural and regulatory virulence V. cholerae genes and can be used for evaluation of newly discovered cholera vibrio strains.